2020
DOI: 10.1111/cfs.12782
|View full text |Cite
|
Sign up to set email alerts
|

Family violence and oppositional defiant disorder symptoms in Chinese children: The role of parental alienation and child emotion regulation

Abstract: Oppositional defiant disorder (ODD) is one of the most common developmental disorders during childhood. The current study examined the mediating role of parental alienation and the moderating role of child Emotion Regulation that had been divided into Lability/Negativity and Emotion Regulation when considering the relation between family violence and ODD symptoms. A sample of 409 children (M age = 9.36, SD = 1.55) and their parent was recruited from 14 primary schools in China. Parents reported on experiences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…This study contributes to existing research by providing evidence of the potential mental health effects associated with children’s exposure of domestic violence (Ahmadzad-Asl et al , 2016; Ferrari et al , 2016; Lacey et al , 2022). The findings support previous studies that have consistently shown a strong link between domestic violence and mental health disorders in children, including attention deficit hyperactivity disorder, conduct disorder, oppositional defiant disorder, generalized anxiety disorder, separation anxiety disorder and mood disorder as forms of mental health disorders found in children (Al Majali and Alsrehan, 2019; Chen et al , 2020; Curtis et al , 2015; Gul and Gurkan, 2018; Kehkashan Arouk, 2017; Okado and Bierman, 2015; Sanderud et al , 2016; Trevillion et al , 2012). These findings align with the research by Aebi et al (2010) and Georgiades et al (2019), which also reported a high prevalence of mental health disorders in children exposure to domestic violence.…”
Section: Discussionsupporting
confidence: 89%
“…This study contributes to existing research by providing evidence of the potential mental health effects associated with children’s exposure of domestic violence (Ahmadzad-Asl et al , 2016; Ferrari et al , 2016; Lacey et al , 2022). The findings support previous studies that have consistently shown a strong link between domestic violence and mental health disorders in children, including attention deficit hyperactivity disorder, conduct disorder, oppositional defiant disorder, generalized anxiety disorder, separation anxiety disorder and mood disorder as forms of mental health disorders found in children (Al Majali and Alsrehan, 2019; Chen et al , 2020; Curtis et al , 2015; Gul and Gurkan, 2018; Kehkashan Arouk, 2017; Okado and Bierman, 2015; Sanderud et al , 2016; Trevillion et al , 2012). These findings align with the research by Aebi et al (2010) and Georgiades et al (2019), which also reported a high prevalence of mental health disorders in children exposure to domestic violence.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, Chen et al (2020) demonstrated that children’s emotional lability/negativity significantly moderated the link between family violence and children’s ODD symptoms, by using a sample of 409 children ( M age = 9.36, SD = 1.55). Consistent with this viewpoint, a higher level of family violence was associated with higher levels of ODD symptoms among children with lability/negativity [ 98 ].…”
Section: Resultsmentioning
confidence: 81%
“…Indeed, considerable research has shown that maladaptive ER competencies are significantly related to the development of child ODD symptoms [ 95 , 96 , 97 ]. More succinctly stated, children with impaired ER competencies appear to be more vulnerable to developing ODD symptoms and other psychopathology [ 98 , 99 , 100 , 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…Family function refers to the interaction of physical, emotional and psychological activities among all family members and is composed of family cohesion and adaptability [11]. Considering the family as a complete unit and system, factors at the entire family level have proved to be closely related to the children's destructive behavior, including the ODD [12][13][14][15].…”
Section: Multilevel Family Model and Oddmentioning
confidence: 99%